Friction and wear behavior of aluminium chromium nitride coating and palm oil methyl ester lubrication - Sebastian Dayou (2013)
This thesis investigates the effectiveness of POME (palm oil methyl ester) as lubricant additive using four-ball and milling tests. Examination on the friction and wear behaviour of AlCrN coating and its comparison to that of TiN coating by using the ball-on-disk and reciprocating tests is also done. Comparative study on the coatings in air and vacuum environment was aimed to provide important insight on the effect of oxidation on the friction behaviour of the coatings. Other important factors such as load, sliding velocity and temperature effects on the coatings were also investigated. Compared to flood lubrication, small quantity of mineral oil sprayed in mist form was more effective in reducing the coating delamination and delaying the occurrence of tool cracking and fracture in the milling tests. The effectiveness of mineral oil in suppressing coating delamination and delaying the occurrence of cracking and fracture could be enhanced by the presence of POME. The mechanism by which the POME suppresses these wear mechanisms could be explained by the results obtained in the four-ball wear tests. The presence of POME brought a reduction in the friction coefficient, severity of welding of the asperities and wear scar, and increased the critical load for welding to occur. In the ball-ondisk tests carried out in vacuum, (i) TiN gave lower COF (coefficient of friction) than AlCrN, showing that the surface of TiN was more lubricous, and (ii) the COF of both coatings were lower than that produced in air. In ambient air, AlCrN gave lower COF than TiN with high wear debris retention on the sliding interface due to the effect of oxidation. In the reciprocating tests, increasing the temperature from room temperature to 150 °C resulted in a reduction in the COF. Higher nominal load resulted in lower COF while higher speed resulted in higher COF. The presented results have shown promising use of POME as additive component in oil lubricant as well as provided fresh insight on the superior oxidation behaviour of AlCrN.